Response of Organic Nutrient Management Practices on Soil Properties and Productivity of Chickpea (Cicer arietinum L.) - Sharma, S. K.; Choudhary, Roshan; Trivedi, Amit; Choudhary, R. S.; Yadav, Shrawan K. (International Journal of Bio-resource and Stress Management, 2017)
Field experiment was conducted on sandy clay loam soil at Instructional Farm, Department of Agronomy, Rajasthan College of Agriculture, Udaipur (Rajasthan), India during rabi seasons of 2012–13, 2013–14 and 2014–15 to study the development of nutrient management practices for production of organic chickpea (Cicer arietinum L.). The experiment was laid out in randomized plot design and replicated thrice with ten treatments. Application of organic manures resulted in significantly higher organic carbon, available nitrogen, phosphorus and potassium as compared to other treatment over three years. The soil applied organic manures and foliar spray of biodynamic manures significantly enhanced the growth and yield parameters of chickpea viz., plant height, number of branches, and number of pods plant-1, 100-seed weight, grain yield and haulm yield. Application of vermicompost 2 t ha-1 as basal+vermicompost 2 t ha-1 at 40 DAS+mustard cake 1 t ha-1 as basal+Rhizobium+PSB+BD-500 75 g ha-1 before sowing and 30 DAS+BD-501 2.5 g ha-1 at 2–4 leaf and pre-flowering stage recorded significantly higher seed yield (1748 kg ha-1), haulm yield (5416 kg ha-1), number of pods plant-1 (114.92) and number of grains pod-1 (1.48) compared to other treatments. Similarly, maximum net return (` 40631 ha-1) was also recorded with application of vermicompost 2 t ha-1 as basal+vermicompost 2 t ha-1 at 40 DAS+mustard cake 1 t ha-1+Rhizobium+PSB+BD-500+BD-501 which recorded an increase of 76.08% and 26.49% higher over control and application of FYM 8 t ha-1+Rhizobium+PSB, respectively.